How does Economic Policy Uncertainty affect Green Innovation? - Fakher, Amjad; Khurshid, Sobia; Naseem, Benish; Rashid, Javeria (Pakistan Journal of Humanities and Social Sciences, 2023)
This study aims to examine the impact of economic policy uncertainty (EPU) on green innovation in the Chinese context. When economic policies are changed often, the Economic Policy Uncertainty (EPU) index rises. There is a dearth of studies examining how EPU affects corporate green innovation. This research shows that between 2007 and 2021, Economic Policy Uncertainty (EPU) would have a negative impact on green innovation inside Chinese corporations. Budgetary restraints cushion green innovation from the negative effects of Economic Policy Uncertainty (EPU). Subsidies for the environment provided by the government may help reduce EPU. Eco-friendly innovation is negatively connected with EPU, especially for privately owned businesses, those in less competitive sectors, and those in locations with weak intellectual property protections. This research suggests that in order to encourage environmentally responsible business innovation, authorities should increase the proportion of public monies spent on environmental protection and IP rights protection. Green innovation is more prevalent in times of high economic policy uncertainty. Different provinces, with varying degrees of marketization and FDI, display varying degrees of Economic Policy Uncertainty (EPU). The findings show that Environmental Policy Uncertainty (EPU) has a greater impact on green innovation in locations with higher degrees of marketization and trade openness compared to regions with lower levels of marketization and trade openness. The current study may be used to the investigation of government methods for fostering environmentally friendly innovation in the face of policy ambiguity.